Caregiver versus self-reported activities of daily living among HIV-positive persons in Rakai, Uganda. Issue 7 (3rd July 2019) - Kisakye, Alice; Saylor, Deanna; Sacktor, Ned; Nakigozi, Gertrude; Nakasujja, Noeline; Robertson, Kevin; Anok, Aggrey; Wawer, Maria; Gray, Ron
ABSTRACT: Assessment of an individual's functional status, as measured by activities of daily living (ADL), is an essential element in the diagnosis of HIV-associated neurocognitive disorders (HAND) but individuals with cognitive impairment may not accurately report ADL. We assessed agreement between self- and caregiver-reported ADL in HIV-positive persons. Antiretroviral therapy (ART)-naïve HIV-positive persons ( n = 321) and HIV-negative controls ( n = 134) in Rakai, Uganda, completed neurocognitive tests and an ADL questionnaire. Co-resident relatives ("caregivers") were independently administered the ADL questionnaire to determine their perception of the participant's ADL. The relationship between neurocognitive impairment and participant-caregiver agreement was assessed using kappa statistics. Regression was used to estimate adjusted prevalence ratios (AdjPR) of participant-caregiver agreement on disability scores. Relative to HIV-negative adults, HIV-positive participants scoring at least 1 standard deviation (SD) below the norm on 2 or more neurocognitive tests were classified as having mild neurocognitive impairment and those scoring at least 2 SD below the norm on 2 or more neurocognitive tests were classified as having moderate-to-severe. Mean age was 36 years (SD 8.9), and 53% of participants were male. The rate of ADL agreement between participants and caregivers was 77% for HIV-positive and 87% for HIV-negative participants (AdjPR = 0.89, 95% CI 0.81–0.97, p = .01). Among HIV-positive participants, 41% had moderate neurocognitive impairment, 15% had severe neurocognitive impairment, and 44% were normal. For moderate neurocognitive impairment, the rate of ADL agreement was 69% and for severe neurocognitive impairment, it was 66%. Compared to non-impaired HIV-positive participants (86% ADL agreement), ADL agreement was lower with moderate impairment (AdjPR = 0.89, 95%CI 0.81–0.98, p = .023) and severe impairment (AdjPR = 0.77, 95%CI 0.63–0.95, p = .014). Gender, education and CD4 count were not associated with ADL agreement. HIV-positive persons with neurocognitive impairment have lower agreement with caregivers' reports of ADL than HIV-positive persons without cognitive impairment.